Derivative Spectrophotometric Method for Estimation of Antiretroviral Drugs in Fixed Dose Combinations - Mohite P.B; Pandhare R.B; Khanage S.G (Tabriz University of Medical Sciences, 2012)
Purpose: Lamivudine is cytosine and zidovudine is cytidine and is used as an antiretroviral agents. Both drugs are available in tablet dosage forms with a dose of 150 mg for LAM and 300 mg ZID respectively. Method: The method employed is based on first order derivative spectroscopy. Wavelengths 279 nm and 300 nm were selected for the estimation of the Lamovudine and Zidovudine respectively by taking the first order derivative spectra. The conc. of both drugs was determined by proposed method. The results of analysis have been validated statistically and by recovery studies as per ICH guidelines. Result: Both the drugs obey Beer's law in the concentration range 10-50 μg mL-1,for LAM and ZID; with regression 0.9998 and 0.9999, intercept - 0.0677 and - 0.0043 and slope 0.0457 and 0.0391 for LAM and ZID, respectively.The accuracy and reproducibility results are close to 100% with 2% RSD. Conclusion: A simple, accurate, precise, sensitive and economical procedures for simultaneous estimation of Lamovudine and Zidovudine in tablet dosage form have been developed.